Public Relations Strategy in Increasing the Number of New Students at SMK Al Ikhsan Blu'uren Sampang - Mokhlis; Maszeri; Faiqaitul munawwarah; Ali Nurhadi; Faidatul Jannah (al-Afkar, Journal For Islamic Studies, 2025)
Facing the competition of institutions in increasing the number of new students is certainly a challenge for institutions. The strategy carried out by SMK Al-Ikhsan is to manage its public relations management. The purpose of this study is to reveal the role and strategy of public relations management at SMK Al-Ikhsan Sampang to increase the number of new students. The method used in this research uses a field-based curriculum approach. The data collection techniques used are observation, interviews, and documentation. The results of this study indicate that the role of public relations is to create excellent programs including industrial cooperation, entrepreneurship programs, and scholarship and award programs. The public relations management strategies carried out include maintaining effective communication and building a positive image, institutions involving parents and the community, conducting promotions, holding events and activities, providing scholarships to outstanding students and finding scholarship information for those who want to continue to college. The conclusion of this study shows that the strategies carried out to increase the number of new students are considered effective as seen from the number of student statistics per year that have increased.